Treatment of posttraumatic epilepsy with new generation antiepileptic drugs (AEDs) – our experience - Lidija Šapina; Marija Ratković (Medicinski glasnik, 2017)
Aim: To investigate influence of therapy with new generation antiepileptic drugs (AEDs) in fastening of posttraumatic epilepsy (PTE) remission comparing to therapy with standard AEDs, as well as the time to remission in the presence of psychiatric comorbidities. Methods: The study was conducted during the 1988-2008 period and included 113 patients (47 females and 67 males) with PTE and 113 patients (93 females and 20 males) suffering from complex partial seizures (CPS) of temporal lobe origin. In both patient groups, epileptic seizure phenotype, brain magnetic resonance imaging (1.5 T and 3.0 T) and electroencephalogram were analyzed within 24 hours of epileptic seizure and after 5 years of treatment. Psychological testing was administered prior to therapy initiation. Results: The patients treated with standard AEDs achieved remission in 82 (73%) cases as compared with 87 (77%) patients administered with a new generation AEDs; in the latter group, remission was achieved faster (1.85 vs. 1.6 months). In both patient groups, psychiatric comorbidity prolonged time to remission by 3.4 months. Conclusion: Therapy with new generation AEDs enables achieving faster and complete remission in PTE patients.
Keywords: classification; epidemiology; surgery; therapy; traumatic brain injury